2011
DOI: 10.1080/02786826.2010.550962
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Extrathoracic Aerosol Deposition using RANS-Random Walk and LES Approaches

Abstract: Computational Fluid Dynamics (CFD) has emerged as a powerful and economical alternative to empiricism in the prediction of aerosol deposition inside the extrathoracic airways (ETA). In RANS-type treatments, a main difficulty is the specification of turbulent fluid fluctuations experienced by the particles, and hence recent research has concentrated on Large Eddy Simulations (LES) in conjunction with Lagrangian Particle Tracking (LPT). While providing close agreement with data, LES/LPT approaches are extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…On the other hand, LES which resolves the large scales in the flow and can therefore better predict turbulent dispersion, has been performed on simplified representations of the models (Matida et al, 2006;Jayaraju et al, 2008;Debhi, 2011;Cui & Gutheil, 2011). Whereas Jayaraju et al (2008) found considerable improvement in predicting deposition for smaller particles and Cui & Gutheil (2011) showed better predictions particularly in the transitional regime using LES over RANS, Debhi (2011) obtained comparable accuracy between RANS and LES models. In addition, experiments have demonstrated the large effect that geometric complexity has on the flow, and hence deposition (Heenan et al, 2004;Grgic et al, 2004b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, LES which resolves the large scales in the flow and can therefore better predict turbulent dispersion, has been performed on simplified representations of the models (Matida et al, 2006;Jayaraju et al, 2008;Debhi, 2011;Cui & Gutheil, 2011). Whereas Jayaraju et al (2008) found considerable improvement in predicting deposition for smaller particles and Cui & Gutheil (2011) showed better predictions particularly in the transitional regime using LES over RANS, Debhi (2011) obtained comparable accuracy between RANS and LES models. In addition, experiments have demonstrated the large effect that geometric complexity has on the flow, and hence deposition (Heenan et al, 2004;Grgic et al, 2004b).…”
Section: Introductionmentioning
confidence: 98%
“…A number of Reynolds-averaged Navier-Stokes (RANS) (Zhang et al, 2002;Heenan et al, 2003;Kleinstreuer & Zhang, 2003;Matida et al, 2004;Jayaraju et al, 2007;Sandeau et al, 2010) and large eddy simulation (LES) studies (Matida et al, 2006;Jayaraju et al, 2008;Debhi, 2011;Cui & Gutheil, 2011) have been reported in the literature. However, accurate prediction of the flow field remains a challenge due to the complexity of the flow in the extrathoracic airways and the limitations of RANS and LES turbulence models.…”
Section: Introductionmentioning
confidence: 99%
“…The time step was set to be 10 -5 to ensure a low Courant-Friedrichs-Lewy (CFL) number (Yin et al, 2010). For realistic complex geometries like the present CT-scan-based lung model geometry, a pure tetrahedral mesh style has been considered appropriate in many past studies De Backer et al, 2008;Dehbi, 2011;Farkas and Balashazy, 2007;Katz et al, 2014;Lambert et al, 2011;Zhang and Papadakis, 2010). In addition, Longest and Vinchurkar (2007) studied the effects of various mesh styles and concluded that the grid convergence was reasonable for tetrahedral mesh.…”
Section: Model Reconstruction Computational Mesh and Numerical Methodsmentioning
confidence: 98%
“…The strong impingement of the ETT-jet at the carina ridge of the main bronchi results in higher friction velocity leading to values of y+ > 1 at specific localized regions near the first bifurcation. y+ ranges from o.5 to 3 for LES has been reported in the literature Banerjee, 2015a, 2015b;Dehbi, 2011;Ghasempour et al, 2014). The mesh sensitivity was examined by computing the resolved turbulence kinetic energy as a percentage of the total energy at critical region in the domain.…”
Section: Model Reconstruction Computational Mesh and Numerical Methodsmentioning
confidence: 99%
“…For coarse particles, the Lagrangian particletracking approach is the most common for low Reynolds number flows, since due to inertial effects particle velocities can differ substantially from the surrounding gas phase, and molecular diffusion is negligible (Shi et al 2007). For high Reynolds number flows, turbulent mixing is typically modeled as a diffusion process, and some studies have adopted a two-fluid Eulerian approach (Mohanarangam et al 2008;Dehbi 2011). Far less common is the use of a two-fluid Eulerian approach for coarse particles in laminar flow.…”
Section: Introductionmentioning
confidence: 99%